Oil Spill in Brazil-Analysis of Vulnerabilities and Socio-Environmental Conflicts - Mariana Olívia Santana dos Santos; Mariana Maciel Nepomuceno; José Erivaldo Gonçalves; Ana Catarina Leite Véras Medeiros; Rafaella Miranda Machado; Caroline Pontes da Silva Santos; Maria José Cremilda Ferreira Alves; Aline do Monte Gurgel; Idê Gomes Dantas Gurgel (MDPI AG, 2022)
The 2019 oil spill was considered the largest environmental disaster in the Brazilian Northeastern coast. It was associated with mostly ineffective government actions, thus intensifying historical vulnerabilities faced by local populations. We aimed to analyze the environmental conflicts and injustices and the socio-environmental, economic, and health vulnerabilities arising from the oil spill, considering the COVID-19 pandemic, impacting artisanal fishing communities of the Northeastern coast. A document-based, qualitative, cross-sectional research was carried out between September 2019 and October 2022, in open access secondary databases, and using field diaries from research of the Environmental Health and Work Laboratory (LASAT) of the Aggeu Magalhães Institute of the Oswaldo Cruz Foundation. The disaster caused situations of injustice and environmental conflicts that had negative repercussions in the territories with socioeconomic impacts, on the environment, and on the health of the population. The entire marine environment was affected, resulting in physical and chemical alterations. The health vulnerabilities faced by local people were intensified, influencing the social determination of the health-disease process. The local economy was extremely affected, generating job insecurity and several socio-cultural problems. It is essential to build environmental and health diagnoses for remedial measures in disasters such as the oil spill.